1987
DOI: 10.1002/j.1460-2075.1987.tb02642.x
|View full text |Cite
|
Sign up to set email alerts
|

An oscillatory mode for microtubule assembly.

Abstract: Depending upon the conditions under which polymerization takes place, pure tubulin can assemble into microtubules following either the usual monotonic kinetics or a more complex oscillatory mechanism. When present, these oscillations involve large cyclic changes in the extent of polymer formed before a steady‐state is reached. Analysis of the microtubules formed at different times shows that these oscillations involve marked redistribution in both the length and number of microtubules. No significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 17 publications
7
63
0
Order By: Relevance
“…The present results also allow us to propose a comprehensive interpretation of the recent observations of Pirollet et al (1987) within our model. These authors reported oscillations of microtubules in the presence of a GTP-regenerating system; total absence of free GTP was an absolute requisite to the observation of oscillations.…”
Section: T-gtp < Isupporting
confidence: 71%
See 1 more Smart Citation
“…The present results also allow us to propose a comprehensive interpretation of the recent observations of Pirollet et al (1987) within our model. These authors reported oscillations of microtubules in the presence of a GTP-regenerating system; total absence of free GTP was an absolute requisite to the observation of oscillations.…”
Section: T-gtp < Isupporting
confidence: 71%
“…Oscillatory polymerization kinetics have also been reported under similar ionic conditions (Pirollet et al, 1987) except that the absence of free GTP was strictly required and the restoration of tubulin bound GTP had to be ensured by a GTP-regenerating system. In the same medium conditions as Carlier et al (1987a), the existence of oscillations has recently been confirmed using synchrotron radiation (Mandelkow et al, 1988).…”
Section: Introductionmentioning
confidence: 86%
“…Pirollet et al [14] have observed oscillations with ultraviolet light scattering, using a GTP-regenerating system. They do not specify a reaction model, but in our view their observations belong to the class of internally forced oscillations.…”
Section: Comparison With Other Published Results On Oscillationsmentioning
confidence: 99%
“…This leads to slow oscillations, with phases of assembly followed by nearly complete breakdown of microtubules. Another example is the experiment of Pirollet et al [14] who use acetate kinase, as discussed later. A computer simulation of this type of oscillation is shown in Fig.…”
Section: Computer Simulation Of Oscillationsmentioning
confidence: 99%
“…Oscillations during microtubule polymerization have been observed either when GTP is regenerated enzymatically from endogenous GDP (guanosine diphosphate) [5,7,9,11] or when some amount of GTP is provided at the beginning or during an experiment. In the latter case oscillations occur only as a transient, because GTP is either consumed or some reactions steps may be inhibited due to the accumulation of GDP [8].…”
Section: Introductionmentioning
confidence: 99%